Evolutionary analysis of Hemagglutinin and neuraminidase gene variation in H1N1 swine influenza virus from vaccine intervention in China - Xinkun Zhao; Mingshuai Shen; Li Cui; Cun Liu; Jieshi Yu; Guisheng Wang; Mihajlo Erdeljan; Kezhou Wang; Shumin Chen; Zhao Wang (Scientific Reports)
Abstract Influenza poses a significant threat to the global economy and health. Inactivated virus vaccines were introduced in China for prevention in 2018. In this study, three pairs of hemagglutinin (HA) and neuraminidase (NA) gene sequences were obtained from three Swine influenza virus (IAV-S) inactivated vaccine strains that were marketed in China in 2018. Phylogenetic analysis was carried out with HA and NA gene sequences to investigate the relationship between vaccine use and virus genetic drift. The findings showed that the evolutionary rate of HA remained relatively stable from 2012 to 2017, with an average genetic distance of approximately 0.020731195. However, following the introduction of the swine influenza vaccine, there was a notable acceleration in the evolutionary rate of HA, accompanied by a significant increase in the genetic distance. In 2018, the value was 0.111750269, while in 2019 it was 0.176389393. In contrast, the evolution of NA was relatively smooth, with an average genetic distance of approximately 0.030386708. Finally, we demonstrated that commercial vaccines are weak neutralizers of wild strains through immunization experiments in animals. Thus, we have reason to believe that mutations in the virus favor virus evasion of vaccine immunity. Our findings suggest that vaccine use may significantly impact the evolution of the influenza virus by potentially stimulating mutations. The selection pressure of vaccine antibodies played a role in regulating the variation of IAV-S-H1N1.